Combined high-dose rate brachytherapy (HDR-BT) and whole pelvic radiation therapy (WPRT) in node negative, intermediate- to high-risk localised prostate cancer: Clinical outcomes and patient behaviours across ethnicities - Apichart Panichevaluk (2018)
© 2017 Cambridge University Press. Background: This retrospective study aimed to report clinical outcomes of high-dose rate brachytherapy (HDR-BT) and whole pelvic radiation therapy (WPRT) in intermediate- to high-risk localised prostate cancer and to gain a better understanding of how behavioural variability of patients from various ethnic origins affects clinical practice. Materials and methods: In total, 116 localised intermediate- to high-risk prostate cancer patients who were treated during 2004-12 were enroled into the study. WPRT was delivered to the full pelvis (50 Gy per conventional fractionation) and two fractions (15 Gy per fraction) of high-dose rate brachytherapy were designed for all patients to the peripheral zone of McNeal. The reported results were biochemical control rate, toxicity profiles and behavioural variations of patients. Results: The median follow-up time was 51 months. The 4-year biochemical control rates, according to the American Society for Therapeutic Radiology and Oncology was 93.1%. T stage was the prognostic factor for biochemical control. No significant differences in biochemical control could be identified across ethnic groups (p>0.05). Five patients developed grade 3-4 gastrointestinal toxicity. Prior knowledge was commonly found among Caucasian patients and urinary functions seemed to be more concerned among Caucasian and Middle East patients than those from other ethnic origins. Conclusions: Clinical outcomes of intermediate- to high-risk prostate cancer patients from various ethnic origins were comparable with that of the Caucasian-only population reported previously. A number of detected ethnic-related factors might be beneficial for treatment decision-making for patients with different cultural background and could be utilised to better personalise/optimise cancer care and aftercare.